2019
DOI: 10.1038/s41467-019-12010-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced propagation of motile bacteria on surfaces due to forward scattering

Abstract: How motile bacteria move near a surface is a problem of fundamental biophysical interest and is key to the emergence of several phenomena of biological, ecological and medical relevance, including biofilm formation. Solid boundaries can strongly influence a cell’s propulsion mechanism, thus leading many flagellated bacteria to describe long circular trajectories stably entrapped by the surface. Experimental studies on near-surface bacterial motility have, however, neglected the fact that real environments have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 61 publications
6
46
0
Order By: Relevance
“…Both moved close to the surface, and individual swimmers displayed different trajectories and without causing significant attractive interaction or "stickiness" on the passive colloids, but both resulted in an enhanced diffusion for these [32]. The absence of "stickiness" was also confirmed by Makarchuk et al, who additionally found an influence on the bacteria's trajectories [33]. Tracer trajectories have been obtained, but since the here simulated swimmers were inspired by biological swimmers (E. coli for pushers and Chlamydomonas as pullers), no clustering of tracers in the surrounding of the swimmers has been observed.…”
Section: Body Deformationmentioning
confidence: 68%
“…Both moved close to the surface, and individual swimmers displayed different trajectories and without causing significant attractive interaction or "stickiness" on the passive colloids, but both resulted in an enhanced diffusion for these [32]. The absence of "stickiness" was also confirmed by Makarchuk et al, who additionally found an influence on the bacteria's trajectories [33]. Tracer trajectories have been obtained, but since the here simulated swimmers were inspired by biological swimmers (E. coli for pushers and Chlamydomonas as pullers), no clustering of tracers in the surrounding of the swimmers has been observed.…”
Section: Body Deformationmentioning
confidence: 68%
“…Looking toward the future, our findings open up new interesting avenues to direct the dynamics and organization of ABPs. Local control over the rotational dynamics offers an alternative means to control the persistence of active trajectories at a given velocity, which can be harnessed to optimize the navigation of ABPs in complex environments 40 , 41 . The introduction of periodic modulations in the rotational dynamics of ABPs also defines a new framework to study a variety of anomalous diffusion phenomena 28 – 31 , beyond the cases presented here, with the emergence of interesting analogies with glassy dynamics, as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Insight can be taken from recent biological experiments. For example, E. Coli bacteria do not just follow the boundaries, but can experience specular scattering events depending on the angle of approach to the obstacle [5]. Their diffusivity increases if a small number of obstacles is added, but decreases upon further increase of the obstacle density.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, the boundary-following mechanism can slow diffusion [27,11], if the particles are trapped for long times around heterogeneities. On the other hand, there arXiv:2007.07948v1 [physics.bio-ph] 15 Jul 2020 is theoretical [33], numerical [34,6,7], and experimental [5,35] evidence that adding obstacles can, under certain conditions, speed up transport. For example, diffusion is amplified if the microswimmers are scattered forward [7], or simply allowed to propagate along connected obstacles [6].…”
Section: Introductionmentioning
confidence: 99%